Red book 2018-2021 report of the Committee on Infectious Diseases - Kimberlin, David W., editor; Brady, Michael T., editor; Jackson, Mary Anne, editor; Long, Sarah S., editor (American Academy of Pediatrics, 2018)
Extending an 8-decade tradition of excellence, Red Book provides the most reliable and clinically useful information on the manifestations, etiology, epidemiology, diagnosis and treatment of more than 200 childhood infectious diseases. The 31st edition provides evidence-based guidance to practicing clinicians on pediatric infections and vaccinations based on the recommendations of the committee as well as the combined expertise of the CDC, the FDA, and hundreds physician contributors. -- Provided by publisher.